Why people photographs : selected essays and review - Adams, Robert (New York : Aperture, 1994)
Contents:## What can help: Colleagues, Humor, Collectors, Writing, Teaching, Money, Dogs ##Examples of success: Edward Weston; Paul Strand; Laura Gilpin; Judith Joy Ross; Susan Meiselas; Michael Schmidt; Ansel Adams; Dorothea Lange; Eugène Atget ##Working conditions: In the nineteenth-century West; In the twentieth-century West; Two landscapes.
boek